2017
DOI: 10.1039/c6ra26028d
|View full text |Cite
|
Sign up to set email alerts
|

Co-immobilization of 1-vinyl-3-octadecylimidazolium cations and p-styrenesulphonate anions on silica and their anti-interference performance for the adsorption of naphthols

Abstract: Adsorptive removals of naphthols are often interfered by some coexisting anions of aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This result demonstrates that the developed porous poly­(2-oxazoline)-based polymers perform better than previously reported materials and can be effectively used for the selective removal of bisphenol S from water solutions. Finally, the q m values obtained for 2-naphthol are also higher than those reported for Fe3O4@polyaniline core–shell nanomaterials (28.7356 mg g –1 ), modified silica (71.9 mg g –1 ), and anion–cation organopalygorskite (33.65 mg g –1 ), indicating that the obtained porous polymers are effective adsorbents for the removal of 2-naphthol.…”
Section: Resultsmentioning
confidence: 61%
“…This result demonstrates that the developed porous poly­(2-oxazoline)-based polymers perform better than previously reported materials and can be effectively used for the selective removal of bisphenol S from water solutions. Finally, the q m values obtained for 2-naphthol are also higher than those reported for Fe3O4@polyaniline core–shell nanomaterials (28.7356 mg g –1 ), modified silica (71.9 mg g –1 ), and anion–cation organopalygorskite (33.65 mg g –1 ), indicating that the obtained porous polymers are effective adsorbents for the removal of 2-naphthol.…”
Section: Resultsmentioning
confidence: 61%
“…The reported adsorbents include carbons activated by KOH, HNO 3 H 3 PO 4 and ZnCl 2 , 17 olive wood biosorbents, 18 UiO-66-NH 2 , 19 glycidyl methacrylate graed cotton cellulose, 20 yellow bentonite, 21 XAD-4 resin, 22 activated carbon bers, 23 layered double hydroxides and their calcined products, 24 carbon nanospheres, 25 date seeds 26 and active carbon. 27 In recent years, ionic liquid-modied silicas (IL-silicas) as adsorbents have been widely used to remove Cu(II), Fe(III), Mn (II) and Ni(II), 28 Pb(II), [29][30][31] Cr(III,VI), [32][33][34] lanthanides and scandium ions, 35 oxymatrine, 36 bovine serum albumin, 37 racemic amino acids, 28 thiophenic sulfur compounds, 38 anionic dye, 39,40 dibenzothiophene 41 and phenolic compounds (4-chlorophenol, 42 polyphenols, 43 phenolic acids, 44 naphthols, 45 bisphenol A 46 and 2,4-DNP [47][48][49] ). To elucidate the relation between the structure of IL-silicas and their adsorption performance for phenolic compounds, a series of IL-silicas were designed by varying substituents, the functional groups of the imidazolium ring, counter ions and silane-coupling agents.…”
Section: Introductionmentioning
confidence: 99%
“…49 In order to overcome the negative effects of coexisting anions on the adsorptive removals of naphthols, a silica adsorbent was prepared through the co-modication of 1-vinyl-3octadecylimidazolium cations and p-styrenesulphonate anions on silica via click chemistry reaction. 45 In addition, imidazole, phenyl and hexadecyl were further co-immobilized onto silica via silane coupling reaction or thiol-ene click chemistry for bisphenol A adsorption from high salt aqueous solutions. 46 The review of literatures showed that one imidazolium-based ionic liquid was oen used to prepare the IL-silicas via silane coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…1-Naphthol is an important raw material for the organic synthesis of pharmaceuticals, pesticides, and dyestuffs (4,5) and is also the major intermediate during the degradation of carbaryl (6), napropamide (7,8), and polycyclic aromatic hydrocarbons (PAHs) (9). Because of its common use, 1-naphthol is frequently detected in soil, water, and even the ocean (10,11).…”
mentioning
confidence: 99%